PENGARUH KOMPENSASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Suatu penelitian Tentang Pengaruh Kompensasi Yang Diberikan Oleh Perusahaan Terhadap Kepuasan Kerja Karyawan di Ambarrukmo Palace Hotel, Sleman, Yogyakarta) - Parsidi, Parsidi (Sekolah Tinggi Pariwisata AMPTA, 2008)
In a company, employee is not solely as object in attain of the purpose like in the eyes of classic, but rather than that employee is a patner. Company’s success also hardly determined by the success of the employee in finalizing the duty. Job satisfaction of intra corporate employee must be created as possible: that morale, dedication, loyality, and employee’s discipline always looked after or even increasingly increases. Employee’s job satisfaction can reached by some steps like: perception of job, motivation and compensation of the job activities.